Cheap talk, fraud, and adverse selection in financial markets: some experimental evidence - Forsythe, R. (Review of Financial Studies, 1999)
Journal Article Cheap Talk, Fraud, and Adverse Selection in Financial Markets: Some Experimental Evidence Get access Robert Forsythe, Robert Forsythe University of Iowa Search for other works by this author on: Oxford Academic Google Scholar Russell Lundholm, Russell Lundholm University of Michigan Search for other works by this author on: Oxford Academic Google Scholar Thomas Rietz Thomas Rietz University of Iowa Address correspondence and reprints requests to Thomas Rietz, Department of Finance, College of Business Administration, University of Iowa, Iowa City, IA 52242, or e-mail: Thomas-Rietz@uiowa.edu. Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 12, Issue 3, July 1999, Pages 481–518, https://doi.org/10.1093/revfin/12.3.0481 Published: 01 June 2015